Discovery and molecular identification of a new orthophasmavirus in the Asian citrus psyllid (Diaphorina citri) - Zhang, Song; Chen, Jing; Liu, Luqin; Xie, Zhipeng; Liang, Jiamei; Yan, Fulin; Song, Yaqin; Wang, Xuefeng; Zhou, Changyong; Cao, Mengji; Liu, Jinxiang (Frontiers in Microbiology, 2025)
IntroductionAsian citrus psyllid (ACP, Diaphorina citri) is the primary vector of Candidatus Liberibacter asiaticus (CLas), a major causal pathogen of citrus Huanglongbing (HLB). HLB remains difficult to control, and exploring viral genomic resources may offer new strategies for managing both CLas and ACPs—either by utilizing viruses as biocontrol agents or as specific delivery vectors.MethodsHigh-throughput sequencing was employed to identify viruses associated with ACPs. A new negative-sense RNA virus, tentatively named Diaphorina citri bunyavirus 2 (DcBV2), was discovered and subsequently characterized. The quantitative distribution of DcBV2 was assessed across various developmental stages of ACPs and in different tissues of adult individuals. To investigate viral transmission patterns, progeny were obtained from mated infected ACP parents and used to feed on host plants. A potential antagonistic interaction between DcBV2 and CLas was explored.ResultsThe complete genome of DcBV2 is 11,690 nucleotides (nt) in length, comprising three segments: large (L, 6,498 nt), medium (M, 3,341 nt), and small (S, 1,851 nt), which encode the L protein with an RNA-dependent RNA polymerase domain, a glycoprotein precursor, and a nucleoprotein, respectively. DcBV2 and another ACP-associated virus, DcBV, are phylogenetically closely related; however, their L proteins shared only 54.59% amino acid sequence identity, indicating that DcBV2 is distinct. DcBV2 was detected in ACP eggs and exhibited higher titers in the salivary glands and guts of adult ACPs. It was also detected in progeny of infected ACPs and in the leaves fed upon by infected individuals. The infection rate of CLas was reduced in ACPs infected with DcBV2, and vice versa.DiscussionDcBV2 was fully sequenced and represents a new Orthophasmavirus species. It is transmitted vertically and possibly horizontally, and appears to compete with CLas in ACPs. These findings lay the foundation for further exploration of DcBV2’s potential in HLB management.